Cheffle - Hameed, Zainab (2017)
Cheffle will be a unique concept restaurant serving fresh and healthy food, having the home style and taste, at affordable prices through encouraging the talent of passionate chefs. The business model / idea will revolve around a process starting from giving opportunities to talented chefs out there, who don’t get a chance to show their skills and receive recognition, to providing healthy food to the customers in the restaurant by giving a different experience. The restaurant will have a different menu every month, evenly distributed with different cuisines having side dishes (appetizers, salads and snacks), main dishes and desserts, cooked by five different chefs each month. The restaurant will be located in one of the most popular area of Lahore (Pakistan) targeting individuals and families for lunch and dinner hours. It will be located in DHA or Gulberg, Lahore owned and operated by two managing partners. Zainab Hameed, the founder/managing director,who had experience of around 3 years in operations management, after getting her degree in Management and Business Computing, and now has increased her business knowledge through MBA degree. She is passionate about cooking and food herself and will be using her management and IT skills to take this idea forward putting her efforts in managing the business and looking at the marketing platforms to promote the concept and setup as it will be playing the most important role in creating the awareness. She will also be handling the marketing activities whereas an accountant will be hired to deal with accounts and POS system activities. M. Ashar Hameed received his Hospitality Management degree from COTHM and was employed by local chain restaurant in Lahore. He will be the General/Restaurant Manager to deal with daily operations along with admin and HR activities. Five assistant cooks will be employed to accompany the five head chefs, chosen through the Youtube Channel process, to help in their cooking. A kitchen manager/Executive Chef will be hired to head all the chefs and look after the processing and making of food and ingredients.